2011
DOI: 10.1111/j.1349-7006.2011.01985.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of tumor/stromal caveolin‐1 expression in breast cancer patients

Abstract: Caveolin-1 (Cav-1) has been extensively characterized in cancer biological research. However, the role of Cav-1 in the interaction between tumor and stromal cells remains unclear. In the present study, we examined Cav-1 expression in tumor cells and stromal cells in breast cancer tissue by immunohistochemical analysis and evaluated its prognostic value in a training cohort. Immunohistochemical analysis of Cav-1 expression was scored as (++), (+) or ()) according to the proportion of positively stained tumor ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 44 publications
1
40
1
Order By: Relevance
“…We and others have previously shown that a loss of stromal Cav-1 is associated with early tumor recurrence, metastasis, tamoxifenresistance and poor clinical outcome in human breast cancer patients. [22][23][24][25][26][27][28][29][30] Similarly, Cav-1 knock-down fibroblasts increase tumor growth, up to ~four-fold, when they are co-injected with increase in glucose uptake, as we observe in stromal fibroblasts that are co-cultured with cancer cells. Figure 12 shows that we successfully created stable Cav-1 knock-down fibroblasts, using an siRNA-based approach.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 90%
See 1 more Smart Citation
“…We and others have previously shown that a loss of stromal Cav-1 is associated with early tumor recurrence, metastasis, tamoxifenresistance and poor clinical outcome in human breast cancer patients. [22][23][24][25][26][27][28][29][30] Similarly, Cav-1 knock-down fibroblasts increase tumor growth, up to ~four-fold, when they are co-injected with increase in glucose uptake, as we observe in stromal fibroblasts that are co-cultured with cancer cells. Figure 12 shows that we successfully created stable Cav-1 knock-down fibroblasts, using an siRNA-based approach.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 90%
“…These findings may explain the prognostic value of a loss of stromal Cav-1 as a marker of a "lethal" tumor microenvironment. [22][23][24][25][26][27][28][29][30] For recent reviews on either Cav-1 or the conventional Warburg effect, please see the following references.…”
Section: Cancer Cells Metabolically "Fertilize" the Tumor Microenviromentioning
confidence: 99%
“…8,10 In this regard, the prognostic value of a loss of stromal caveolin-1 (Cav-1; indicative of glycolysis and autophagy in the tumor microenvironment) has now been independently validated in seven different countries, and its predictive capacity has also been extended to DCIS progression, human prostate cancers and metastatic melanoma. 8,10,[35][36][37][38][39][40][41] In addition, the expression of stromal MCT4 appears to inversely correlate with stromal Cav-1, allowing them to be used together as companion diagnostics for the detection of "two-compartment tumor metabolism." 31 However, in addition to these stromal diagnostics, new epithelial biomarkers are desperately needed to identify the corresponding onset of mitochondrial biogenesis in human breast cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…22,74,[78][79][80] Consistent with these findings, a loss of stromal Cav-1 is a powerful biomarker for a lethal tumor microenvironment, in breast and prostate cancers. 37,[81][82][83][84][85][86][87][88][89] More specifically, in breast cancer patients, a loss of stromal Cav-1 is associated with early conditions, most of the DNA damage occurs in the cancer-associated fibroblasts, as the MCF7 cancer cells effectively mount an anti-oxidant defense by upregulating key proteins, such as peroxiredoxin-1 and TIGAR.…”
Section: Hydrogen Peroxide and The Lactate Shuttlementioning
confidence: 99%